2015
DOI: 10.1007/s00705-015-2581-1
|View full text |Cite
|
Sign up to set email alerts
|

Losartan and enalapril decrease viral absorption and interleukin 1 beta production by macrophages in an experimental dengue virus infection

Abstract: The role of angiotensin II (Ang II) in dengue virus infection remains unknown. The aim of this study was to determine the effect of losartan, an antagonist of the angiotensin II type 1 receptor (AT1 receptor), and enalapril, an inhibitor of angiotensin I-converting enzyme (ACE), on viral antigen expression and IL-1β production in peritoneal macrophages infected with dengue virus type 2. Mice treated with losartan or enalapril and untreated controls were infected intraperitoneally with the virus, and macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
(34 reference statements)
0
24
0
Order By: Relevance
“…RAS has always been studied with focus on its role in metabolic syndromes such as obesity and hypertension (Van Vark et al, 2012 ; Santos et al, 2013 ; Cabandugama et al, 2017 ); however, its importance in the viral infection process has only recently been observed, as demonstrated by a study in which DENV-infected rats were treated with either losartan or enalapril. In this case, the treatment decreased DENV absorption by macrophages, showing that the RAS may be associated with infection severity (Hernández-Fonseca et al, 2015 ). In an experiment carried out with knockout rats for the angiotensin II converting enzyme (ACE2) and wild-type rats, both infected by the respiratory syncytial virus (RSV), knockout rats presented a five-fold higher viral titer than wild-type rats, in addition to increased pulmonary injury, mortality and angiotensin II (Ang II) plasma concentrations (Gu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…RAS has always been studied with focus on its role in metabolic syndromes such as obesity and hypertension (Van Vark et al, 2012 ; Santos et al, 2013 ; Cabandugama et al, 2017 ); however, its importance in the viral infection process has only recently been observed, as demonstrated by a study in which DENV-infected rats were treated with either losartan or enalapril. In this case, the treatment decreased DENV absorption by macrophages, showing that the RAS may be associated with infection severity (Hernández-Fonseca et al, 2015 ). In an experiment carried out with knockout rats for the angiotensin II converting enzyme (ACE2) and wild-type rats, both infected by the respiratory syncytial virus (RSV), knockout rats presented a five-fold higher viral titer than wild-type rats, in addition to increased pulmonary injury, mortality and angiotensin II (Ang II) plasma concentrations (Gu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 87%
“…All biomarkers were elected and validated by statistical analysis, and are in consonance with previous studies that were focused on proteins (kinases and phosphorylases) involved in the infection process, whilst the biomarkers presented herein are substrates/products of these enzymes. Studies on viral infections, such as DENV and H5N1 have explored the inhibition of ACE (Tikellis et al, 2011 ; Zou et al, 2014 ; Hernández-Fonseca et al, 2015 ; Gu et al, 2016 ) and kinases involved in the PI3K-AKT-mTOR pathway (Easton et al, 2005 ; Tokuda et al, 2010 ; Liang et al, 2016 ); seven out of the eight biomarkers reported in this contribution are directly related to these enzymes, corroborating the relevance of these molecules and providing the targets in which substrate they work. Therefore, the metabolomic insight on human infection by ZIKV provided by this contribution broadens the knowledge of the pathophysiological aspects of the disease by elucidating molecular targets of the cell immune response facing viral infection and replication; this also provides grounds for further developments within the field of pharmacology for differential therapies, interventions and insights in ZIKV infection management.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, studies have reported that the blockade of angiotensin II type 1 (AT1) receptors with losartan and inhibition of angiotensin I-converting enzyme with enalapril reduced the percentage of macrophages expressing DENV2 antigens in vivo, suggesting a decrease in viral entry and a potential role of Ang II in DENV infection. 15 The mechanism by which Ang II affects dengue viral entry remains unclear; however, viral interaction with AT1 or phagocytic receptors could be involved. 15 The concurrence of COVID-19 and dengue fever should be carefully reported and followed with enhanced surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients with Marfan syndrome, Losartan as treatment reduced the rate of dilation of the aortic arch [ 19 ]. In addition, Losartan and Enalapril were capable of reducing the expression of IL-1β in macrophages [ 20 ] and polymorphonuclear leukocytes from patients with essential hypertension [ 21 ].…”
Section: Introductionmentioning
confidence: 99%